The Influence of Professional Skepticism, Independence and Training on Internal Auditor Skills in Detecting Fraud - Claresta Difa Andani; Cris Kuntadi (Jurnal Stagflasi : Ekonomi, Manajemen dan Akuntansi, 2024)
This literature review explores the influence of skepticism, independence, and training on internal auditors' ability to detect fraud. Through analysis of related literature, this research presents important findings from previous studies regarding how these factors influence internal auditors' ability to identify fraudulent acts. By combining existing research results, this review provides an in-depth understanding of the importance of skepticism, independence and training in strengthening the internal audit function in maintaining the integrity and reliability of an organization's financial reports. Practical implications and directions for future research are also considered.